Assessing the effectiveness of conservation policies related to increasing protected areas and their impact on biodiversity loss (2024)
The cornerstone or mechanism of environmental sustainability has been the different facets in which protected areas have been qualified, in general they are one of the most important conservation measures implemented to reduce biodiversity loss. Based on impact assessment methods, in this thesis I have identified the effect of increasing protected areas and their impact on biodiversity loss. The hypothesis is that an increase in terrestrial protected areas contributes to the conservation and protection of biodiversity as assessed by the Red List Index (RLI), Species Habitat Index (SHI), Biodiversity Intactness Index (BII), tree cover loss and abundance of endemic plants. Experimental results show that there is no clear overall effect of protected areas in reducing biodiversity loss. Dynamic results are presented, i.e. results that occur over a specific period, such as for RLI and tree cover loss. In summary, there is no strong evidence of a clear effect of protected areas on biodiversity loss. The results call for more research into what makes some protected areas more effective than others. This dissertation is useful because it has potential applications at both global and regional scales for assessing the effectiveness of protected areas that share territorial spaces, such as borders and strategic ecosystems.